Cooperativismo e assentamento rural na percepção do uso coletivo e individual da terra mediante metodologia Q: o caso de Charqueadas - Santalucia, Maurício (2006)
The cooperativism executed in the CPA (Land-production Cooperatives), stimulated by the MST (Movimento dos Trabalhadores Rurais Sem Terra Movement of Landless Workers), where possession of land and production are under the control of the cooperative, represents a model which is scarcely employed and, throughout the years these CPAs presented internal conflicts among some of its members, that preferred to work individually. The goal of this research is to analyze the subjectivity of rural settlement members located in the county of Charqueadas (RS), divided in two groups: i) those that are working under the integral perspective, (CPA) and ii) those who choose to work individually. The idea was to know the general point of view of these groups in relation to the individual and collective use of land. For this, we used the Q methodology that combines qualitative techniques such as in-depth interviews and qualified informers and quantitative techniques such as factorial statistical analyses of data. In the implementation of the methodology people were interviewed as qualified informers, where the most important set of 41 statements were selected and presented to 40 members of the rural settlement, divided between 20 from the integral model (CPA) and 20 from the individual model. The 41 statements were classified according to their importance in a pre-determined table and the data was analyzed and interpreted using a special statistical software program called PCQ. The results of the factorial analysis show that 5 factors emerged: i) one factor completely in favor of the individual approach, and ii) four factors in favor of collective approaches, with differences among them. In this sense, one factor was completely pro collective, and three factors were pro collective but with criticism to the model. According to the affirmations, the pro individual group believes the CPA experience was a mistake. For the other 4 pro collective groups, 1 of them was satisfied with the organization, and the other 3 groups demonstrated criticism and safeguard to collective model. The pro collective group and the pro individual group selected the same statements but were ranked inversely. It was also observed that in the other three collective groups there were insatisfactions in some aspects of the functioning of the CPA and that improvements could be made in these areas: i) solidarity among members, ii) inducement and centralization in the decision making process, and iii) encouragement to productivity.